2023
DOI: 10.1007/s10067-023-06664-y
|View full text |Cite
|
Sign up to set email alerts
|

Adult-onset Still’s disease complicated by macrophage activation syndrome during pregnancy: a case-based review

Abstract: Adult-onset Still’s disease is a rare, systemic inflammatory rheumatic disease characterized by recurrent fevers, arthritis, and an evanescent rash. One of the most serious hematologic derangements that can be seen with adult-onset Still’s disease is macrophage activation syndrome. Macrophage activation syndrome is characterized by activation of lymphocytes, resulting in a cytokine storm and hemophagocytosis in the bone marrow, along with multi-organ failure. Adult-onset Still’s disease with macrophage activat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…conditions and the need for a multidisciplinary approach in managing these complex clinical scenarios. 13 Dunn et al reported a case of Hemophagocytic Lymphohistiocytosis (HLH) in a 41-year-old pregnant woman with twins, who initially presented with symptoms consistent with HLH and a history of Still's disease. The patient showed a favorable response to high-dose corticosteroids.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…conditions and the need for a multidisciplinary approach in managing these complex clinical scenarios. 13 Dunn et al reported a case of Hemophagocytic Lymphohistiocytosis (HLH) in a 41-year-old pregnant woman with twins, who initially presented with symptoms consistent with HLH and a history of Still's disease. The patient showed a favorable response to high-dose corticosteroids.…”
Section: Accepted Manuscriptmentioning
confidence: 99%